Comparison of psychometric characteristics and factor structure of the scale for measuring general attitudes and pharmacists' beliefs about their own work with patients - Jocić, Dragana; Krajnović, Dušanka (Archives of Pharmacy, 2022)
The initial general pharmacists’ attitudes and beliefs scale about their own work with patients was constructed by D. Jocić, D. Krajnović in 2012. It includes cognitive, affective and behavioral claims. The scale was applied multiple times, followed by validation. The aim was to check the movement of the measuring characteristics of the scale. The study combined 2 studies. In Study 1, a sample of 123 licensed pharmacists validated the initial instrument and proposed a new developed version. In Study 2, on a sample of 514, the validity of the scale and high reliability parameters were confirmed. In Study 1, reliability was determined by the internal consistency method (Cronbach's alpha: 0.670). Factor analysis of principal components was performed and seven factors with latent roots greater than 1 were obtained (explain 64.92% of total variance and 30.84%, 8.20%, 6.55%, 5.63%, 5.01%, 4.68% and 4.01%, respectively. Some claims in the scale are excluded, the final version of the scale contains of 23 claims. In study 2, greater reliability was obtained. The reliability and internal consistency of the subscales were assessed (Cronbach alpha: Cognitive Attitudes 0.774, Affective Attitudes 0.849, Behavioral Attitudes 0.867). The correlations between the scales were extremely high (2). The developed scale also met the statistical criteria of reliability during the first application, and based on these results, the effectiveness could be assumed. Research on a larger sample showed even better psychometric characteristics. Further research on a larger and more heterogeneous sample may show exceptional psychometric characteristics.